The Effect Of Student Learning Motivation on MTS Students' Mathematic Communication Ability - Zharifatul Aqilah; Yenita Roza; Maimunah Maimunah (Universitas Negeri Makassar, 2021)
This study aims to determine whether there is an effect of student learning motivation on mathematical communication skills. The respondents in this study were 32 students from MTs Negeri Karimun, Kepulauan Riau. A test of mathematical communication abilities and a student learning motivation questionnaire were used. A quantitative descriptive study was used as the research method in this study. Simple linear regression analysis was utilized to analyze the data, with student learning motivation as the independent variable and mathematical communication abilities as the dependent variable. The results of the analysis demonstrate that student learning motivation has an effect on mathematical communication skills, with a=5%.